THE ROLE OF MORALITY IN MEDIATING THE RELATIONSHIP BETWEEN RELIGIOSITY AND ACADEMIC INTEGRITY IN STUDENTS - Muhammad Syamsul Hadi; M. Zuhdi Zainul Majdi (Universitas Islam Negeri Mataram, 2025)
Prevent academic cheating, a significant component of the academic culture is academic integrity. Religious and moral values can be used to predict academic integrity. The goal of the research is to understand how morality affects how students' academic integrity and religiosity connect. A quantitative kind of explanatory correlation is used in this research. employing simple random sampling methods to select the subject. There were 60 respondents in the survey. Three instruments—the academic integrity scale, the religiosity scale, and the morality scale—are used to collect data. Data analysis used bootstrapping bias-corrected path analysis based on regression and mediation with a 95% confidential interval. The findings of this research indicate that morality can participate a mediating role in the connection between religiousness and academic integrity